Exploring the Revolutionary Impact of YAP Pathways on Physical and Rehabilitation Medicine - Carmelo Pirri (Biomolecules)
Cellular behavior is strongly influenced by mechanical signals in the surrounding microenvironment, along with external factors such as temperature fluctuations, changes in blood flow, and muscle activity, etc. These factors are key in shaping cellular states and can contribute to the development of various diseases. In the realm of rehabilitation physical therapies, therapeutic exercise and manual treatments, etc., are frequently employed, not just for pain relief but also to support recovery from diverse health conditions. However, the detailed molecular pathways through which these therapies interact with tissues and influence gene expression are not yet fully understood. The identification of YAP has been instrumental in closing this knowledge gap. YAP is known for its capacity to perceive and translate mechanical signals into specific transcriptional programs within cells. This insight has opened up new perspectives on how physical and rehabilitation medicine may exert its beneficial effects. The review investigates the involvement of the Hippo/YAP signaling pathway in various diseases and considers how different rehabilitation techniques leverage this pathway to aid in healing. Additionally, it examines the therapeutic potential of modulating the Hippo/YAP pathway within the context of rehabilitation, while also addressing the challenges and controversies that surround its use in physical and rehabilitation medicine.